Role of the Dinucleotide Signaling Molecule Diadenosine Tetrephosphate in Staphylococcus aureus Pathogenesis - Jackson Corker (UNC Test Journal, 2024)
Staphylococcus aureus can cause a wide range of infections in humans from skin and soft tissue infections to more severe pneumonia, osteomyelitis, bacteremia, and endocarditis, in part aided by its ability to naturally resist the innate immune system. In addition to its pathogenicity, drug resistant strains have emerged in both community and hospital settings. The ability of methicillin-resistant Staphylococcus aureus (MRSA) to resist immune cell-produced nitric oxide (NO·), and to effectively form antimicrobial-resistant biofilms makes it an important pathogen to study. Recently, the S. aureus enzyme YqeK was discovered to degrade the dinucleotide molecule, Ap4A, which has not previously been studied in S. aureus. In other bacteria, elevated Ap4A reduces antibiotic and stress resistance as well as biofilm formation. Here, we created a yqeK deletion mutant in a community-acquired MRSA strain (LAC) and assessed its fitness during both NO resistance and biofilm formation. Relative to wild-type, the yqeK deletion strain demonstrated a significantly decreased ability to resist NO, a decreased ability to form biofilms on polystyrene plates, and a decreased ability to form biofilms on human plasma coated plates. Future work will include RNA-sequencing to determine how gene expression differs in the yqeK deletion strain in order to identify a possible mechanism for these phenotypes and further explore the potential of YqeK or Ap4A as drug targets.